Faktor-Faktor Yang Mempengaruhi Kualitas Pelayanan Publik Di Puskesmas Bahu Kecamatan Malalayang Kota Madya Manado - Soputan, Jultje; Lengkong, Daicy; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research aims to know the factors that affect the quality of public services in Public HealthCenter Bahu, Malalayang Subdistrict Municipality of Manado, as well as to get an idea of the existingpublic services in Public Health Center Bahu, Malalayang Subdistrict municipality of manado. PublicHealth Center is spearheading the development of healthcare in the absence of successful neighborhooddistricts. Health development is an effort meet one of the basic rights of the people, namely people's rightto obtain access to healthcare needs. The main problem as a health service that many of its competitors isthe service given is it appropriate or not public expectation therefore, Public Health Center Bahu,Malalayang Subdistrict municipality of manado is expected to always maintain the trust and satisfactionof the public by increasing the quality of service to the satisfaction of the patients improved. Public HealthCenter Bahu, Malalayang Sub district municipality of manado need to carefully determine the needs ofpatients in an effort to meet the expectations or desires and increase the satisfaction of services provided.The research methods used in this study is a qualitative method, with the techniques of primary andsecondary data collection is done with the interview, observation and documentation study. As for therespondents/informants of this research is the head of the Public Health Center Bahu: 4 employees andhealth workers of Public Health Center: 5 community representatives 5 wards that constitute the coverageof the Public Health Center Bahu, among others, is the village's Bahu, Kleak, Winangun I, Winagun II,and Batu Kota.The results showed that in view of the quality of public services for the Public Health Center Bahu iscurrently said to be the maximum. It happened because of the speed and timeliness in providing theservice is still at a slow rate. From the above problems then in view of the factors that affect the quality ofpublic services, such education, experience, compensation, and work environment, so many problems thatarise from aspects of the four points above, with regard to the central issues that are encountered in termsof placement of employees who do not comply with the skills possessed by these employees, the lack ofofficers, while the work load is very much in compensation, received highly lacking and is not appropriate.In doing Ministry employee also in this still very less experience in taking care of the Administration andothers, in addition to facilities and infrastructure in support of public service which is still very minimal,problem employee discipline and communication problems among fellow employees also should be on theincrease.Referring to the discussion and the conclusions above, in order to improve the quality of recommend inpublic services in Public Health Center Bahu then recommend it – it is as follows. The first need for theattention of the local authorities with regard to infrastructure work supporting employees, the need foradditional employees at the clinics this shoulder, as well as the need for attention from the localGovernment regarding the compensation of employees and the health workforce in the value is still verysmall. Then the need for oversight of the performance of officers so that they can work properly and atmaximum, while leaders must also be able to embrace all officers preparing a time to encourage andmotivate each other between one another, so that in one instance appears mutual respect and had eachother.Keywords: factors that affect the quality of public services